Transforming preschool teacher’s role: From implementer toward researcher - Dragana PAVLOVIĆ BRENESELOVIĆ; Živka KRNJAJA (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi)
In this paper, we start from the conception of the preschool teacher’s role as researcher and the perception of teacher research in the function of practice transformation. The aim of our research was to analyze the research dimension of the pre-school teachers’ practice. The projects reports of 127 teachers who participated at the Annual Conference of Preschool Teachers have been analyzed by coding the data in content analysis matrices. The teachers’ reports were analyzed through four questions: What do preschool teachers state as reasons and aims of their projects? Which dimensions of a research process they cover by their projects? How do they document and evaluate the process and the effects of the project? What do they see as benefits of the project? The analysis has shown that the pre-school teachers do not generally conduct projects in the function of reflection and transformation on their own practice. By qualitative technique of data synthesis, we identified three project models with non-research ones dominating